POLITICAL BEHAVIOUR PATTERNS OF THE USE OF BEGINNER VOTERS’ SUFFRAGE FOR LEGISLATIVE AND PRESIDENTIAL ELECTIONS IN YOGYAKARTA CITY 2019 - Supriyadi; Astuti, Tri Marhaeni Pudji; Masrukhi; Triatmaja, Hamdan (International Journal of Psychosocial Rehabilitation, 2020)
Democracy is a social interaction between a government that has power because they are elected and individual citizens who choose them based on the values of justice. Inside there is the political behaviour of the government as a political decision-maker, implementation, enforcement, and political behaviour of citizens regarding their interests. The holding of general election 2019 as a realization of democracy in Indonesia, provides an opportunity for every citizen as a voter, including beginner voters to use political rights, namely their suffrage. This paper aimed to reveal the political behaviour of the beginner voters in the city of Yogyakarta, both the position/role, meaning, and use of their suffrage in the presidential and legislative elections in Indonesia in 2019. A qualitative approach was used to understand the phenomena experienced by research subjects. Determination of the subject used purposive sampling technique mainly to detail the specificity of information in a unique context. Subjects consisted of voters who vote for the first time, whether they were still in high school and/or equivalent, and who were not in school. Data collection was done through in-depth interview techniques. The results showed that the beginner voters in the city of Yogyakarta, had the potential to participate in developing the political life of democracy, could play a role in its position in the electoral arena, both as a committee, election witnesses, patterns of behaviour and their views on the campaign, the meaning of election meanings, and patterns the behaviour of deciding choices in presidential and legislative elections in Indonesia in 2019.